2001
DOI: 10.1007/s001070050484
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of knot diameter in Picea abies (L.) Karst

Abstract: Knot diameters were measured in 60 trees of Picea abies (L.) Karst. from three different site indexes in southeastern Norway. Ten branch whorls were sampled from each tree, and diameters of all the knots were measured at the radial stem plane. Knot diameter was evaluated as mean diameter of the two thickest knots in each sample whorl. The whorl with the maximum value in each tree was on average located at 30% of tree height at G11, 40% at G17 and 60% at G23. The vertical location was related to the position of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
1
9
0
1
Order By: Relevance
“…DBH is known to be a very strong predictor for branch dimensions of P. abies at individual tree level (Colin & Houllier, 1992;Vestøl et al, 1999;Vestøl & Høibø, 2001;Moberg, 2006). This fact was supported here by the strong phenotypic correlation found (r p 00.83).…”
Section: Discussionsupporting
confidence: 76%
“…DBH is known to be a very strong predictor for branch dimensions of P. abies at individual tree level (Colin & Houllier, 1992;Vestøl et al, 1999;Vestøl & Høibø, 2001;Moberg, 2006). This fact was supported here by the strong phenotypic correlation found (r p 00.83).…”
Section: Discussionsupporting
confidence: 76%
“…Besides site index and geographical data, timber properties also depend on silviculture, cross-cutting and sorting, and these factors are not taken into account in these models. The variance component analysis and the models assume equal variance due to trees and residual variance across sites, but studies have shown that both the difference between trees and the longitudinal variation in knot size is larger on sites with higher site index (Moberg 2001;Vestøl & Høibø 2001). This means that there is a stronger effect of silviculture on stands with higher site index, and with appropriate silviculture it is possible to obtain better timber properties than predicted by the presented models.…”
Section: Discussionmentioning
confidence: 75%
“…Vestøl et al (2012) found that density was somewhat more dependent on site than the bending properties were in a local study in Norway. More dominant trees in a forest stand have both larger knots (Colin & Houllier 1991;Høibø 1991;Vestøl & Høibø 2001) and lower wood density (Høibø 1991;Vestøl et al 2012;Høibø et al 2014). Both these effects lead to lower MOE and MOR in timber from more dominant trees.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, low planting densities may result in thick branches in the most valuable section of the log [6][7][8][9], while planting with high stocking density can effectively reduce the maximum and average branch size [10][11][12][13]. Some studies have also demonstrated that the angle of live branches became steeper with increasing planting densities [14,15], and a more acute branch angle might have the potential to cause larger dead knots and higher knot-related defects [14].…”
Section: Introductionmentioning
confidence: 99%